Optimization of multi quantum well solar cell - Prażmowska, Joanna; Korbutowicz, Ryszard (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Quantum well solar cell with GaAs wells and AlxGa1–xAs barriers was optimized. Particular emphasis was placed on enhancing the efficiency. Open-circuit voltage, short-circuit current density, fill factor have been also optimized. Many simulations of various structures were carried out. The conversion efficiency exceeding 27% was obtained. The algorithm of structures optimization that gives comprehensive information about solar cells parameters in a short time was shown. Spectral characteristics, efficiency of energy conversion as a function of light concentration, temperature and the geometrical and materials parameters of the solar cells structures were determined. These results are compared with nearly identical p-i-n solar cells: i) the first with i-region made from undoped GaAs (well material) and ii) the second with i-region from Al0.1Ga0.9As (barrier material).
Optica Applicata, Vol. 35, 2005, nr 3, s. 619-626
Keywords: optyka; solar cell; quantum well; optimisation; AIIIBV; GaAs; AlGaAs